Corrigendum - Admin AML-CFT Journal (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
Corrigendum to “Potential for the Misuse of Foundations’ Annual Reports in the Commission of Money Laundering Crimes” In the original publication of this article, the author submitted a correction to Table 1, as all columns in the table had been checked. This inaccuracy could potentially lead to misinterpretation. The correction was proposed to ensure data accuracy and provide information that aligns with the contents of the foundation’s annual report.